2015
DOI: 10.1016/j.juro.2015.06.080
|View full text |Cite
|
Sign up to set email alerts
|

Prolapse Recurrence after Transvaginal Mesh Removal

Abstract: At a mean 2.5-year followup 62% of patients (32 of 52) did not have recurrent or persistent prolapse after transvaginal mesh removal and 85% (44 of 52) did not undergo any further procedure for prolapse. Specifically for pelvic organ prolapse in the same compartment as transvaginal mesh removal 12% of patients had recurrence, of whom 8% underwent prolapse repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Tijdink et al [33] reported a 12% recurrence rate and that POP recurrence was found to be more common in patients undergoing complete mesh removal compared to partial excision. Rawlings et al [58] reported a 15% rate of recurrent POP after mesh removal. Marcus-Braun and von Theobald [40] reported a recurrent POP rate of 19%.…”
Section: Outcomes Of Complete Vs Partial Removal Including Complicatmentioning
confidence: 99%
See 2 more Smart Citations
“…Tijdink et al [33] reported a 12% recurrence rate and that POP recurrence was found to be more common in patients undergoing complete mesh removal compared to partial excision. Rawlings et al [58] reported a 15% rate of recurrent POP after mesh removal. Marcus-Braun and von Theobald [40] reported a recurrent POP rate of 19%.…”
Section: Outcomes Of Complete Vs Partial Removal Including Complicatmentioning
confidence: 99%
“…Marcus-Braun and von Theobald [40] reported a recurrent POP rate of 19%. Further, the rate of subsequent POP repair has been shown to range from 0% to 17% [58]. Again, the wide variability in rates of recurrent POP may be related to the method of defining recurrent POP and how much of the original mesh graft was actually removed.…”
Section: Outcomes Of Complete Vs Partial Removal Including Complicatmentioning
confidence: 99%
See 1 more Smart Citation